Perspective of special education teacher’s towards student learning disabilities with challenging behavior/ Shahidatul Hanisah Hamidi and Rosilah Wahab - Hamidi, Shahidatul Hanisah; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This study desired to determine the perspective of special education teachers towards challenging behavior among children with learning disabilities. Participants was ninety six teachers was observed ninety six students with learning disabilities, respectively the students must be attending the school of special education in the integrated program and the teachers must have experience with the students for more than 2 months. The teachers completed the Development of behavior checklist teacher version DBC-T(Einfeld & Tonge,1995). The result of this study showed that there is no significant level of challenging behavior among student with learning disabilities and there is no significant between the level of challenging behavior and age of students with learning disabilities. There is no significant between the level of challenging behavior and gender of the students. The theoretical and practical implications were discussed in this study.